Mpox vaccination hesitancy and its associated factors among the general population in China: A national observational study - Shunzhe Wu; Jie Deng; Min Du; Min Liu; Jue Liu (Human Vaccines & Immunotherapeutics, 2025)
Mpox, formerly known as monkeypox, has been spread to more than 100 countries until now. Vaccines are vital measures to protect against mpox infection. However, vaccine hesitancy remains a barrier to achieving widespread vaccination coverage. We aimed to investigate the prevalence of mpox vaccination hesitancy and its associated factors in China. We conducted a cross-sectional survey among 3669 participants aged 18 years and above in China from September 15 to October 9, 2024. The main outcomes measured were the hesitancy to get vaccinated against mpox for oneself and for one’s children. Data were analyzed using chi-square tests and logistic regression model. The overall hesitancy rate for mpox vaccination was 28.4% for oneself and 24.5% for one’s children. Higher hesitancy was observed among male individuals (30.8%), those aged >40 years (31.2%), married individuals (29.6%), and those with high mpox-related knowledge (30.9%). Multivariable logistic regression analysis showed that females had lower hesitancy (aOR = 0.84, 95% CI: 0.72–0.97), while individuals with high mpox-related knowledge had higher hesitancy (aOR = 1.23, 95% CI: 1.03–1.47). These findings provide valuable data for public health authorities to design effective strategies for mpox vaccination rollout in China.